An Improved Wavelet Digital Watermarking Software Implementation - Khalifa, Othman Omran; Yusof, Yusnita; Hassan Abdalla Hashim, Aisha; Olanrewaju, Rashidah Funke (2012)
There are quite a number of researches in proposing digital image watermarking using Discrete Wavelet Transform (DWT). However, it is clearly observed that each of them is individually distinctive in terms of its scopes and applications. In this paper, a proposed system was thoroughly explained. It includes general work flow, proposed algorithms for both original method and improved method, which were named as subband matching and selective subband matching, respectively and various attacks performed for evaluation. Modification was made to the algorithms where only selected matching subbands were used in embedding and extracting the watermark in this improved method. These methods were compared and tested against attacks using standard benchmark, Stirmark. Experimental results of the proposed methods’ performance were analyzed using Peak Signal to Noise Ratio (PSNR) calculations and Structural SIMilarity (SSIM) index for watermark imperceptibility and robustness, respectively. The improvement could be seen in quality of the watermarked image (imperceptibility) and of extracted watermark (robustness).